THE FUTUROLOGY AND THE KNOWLEDGE OF THE TICS IN THE SMES OF BOYACA-COLOMBIA-DEPARTMENT (2012)
AbstractThis investigation presents the process of the use of the futurologyand the knowledge of the technologies of the information and communication“TICs” in the SMEs of Boyacá department - Colombia. In thedevelopment of the study there were established the theoretical elementsthat support the above mentioned investigation. In the methodologicalaspect the study proposed by the CEA was born in mind, Cepal, and theOSILAC, who elaborated a few key indicators for the measurement of thetics in the companies, with base in this information I design the instrumentto apply to 62 SMEs of the region, belonging to the different economicsectors, located in the municipal head-boards of the department ofwhich relevant information was obtained for the above mentioned study.